Culturally responsive teaching in one urban school district: a needs assessment - Robinson-Woods, Cecilia (My University, 2022)
There exists a pattern of underperformance in minority children in urban school districts across this country. Nationally, minority students—especially African American students—score lower on standardized assessments than non-minority peers (NCES, 2020). Ladson-Billings (1995a), Gay (2000), and Villegas and Lucas (2002) contribute seminal research and provide a foundation for using culturally responsive instructional practices as a method for producing high academically performing African American students. In general, teachers have not been expected to teach in culturally responsive ways for minority students, nor have they been adequately trained in the ability to create and incorporate pedagogical practices that have relevance and meaning to students’ social and cultural realities (Howard, 2003). Bandura (1997) posits that if teachers possess self-efficacy in their teaching practices, they can meet the needs of students. This dissertation examines the perceived overall level of Culturally Responsive Teaching Self-Efficacy among teachers regarding curriculum and instruction, classroom management, student assessment, and cultural enrichment in the target school district. This study utilizes Siwatu’s (2007) Culturally Responsive Teaching Self Efficacy (CRTSE) tool to survey pre-kindergarten through grade 12 teachers in 2018 and 2021, in a predominately African American small midwestern school district, servicing 1,100 students. The CRTSE was originally utilized to help gauge teachers' pre-service dispositions towards their ability to utilize Culturally Responsive Teaching (CRT), which is defined herein as the reflection on and consideration of the relationship between culture and learning (Siwatu, 2007). Utilizing CRT, teachers acknowledge student differences and incorporate those varied experiences that individual cultures create to fashion environments and pedagogy for all learners while emphasizing self-advocacy. Culturally Responsive Teaching has become increasingly important as the demographics of our public schools are increasingly shifting. In 1999, the teacher population was 84% white and today, it has changed to 79%, which guarantees that most children in public schools will be taught by a teacher that does not identify as an ethnic minority (NCES, 2020). An analysis of the CRTSE data revealed that teachers in both data sets (41 and 47 teachers respectively) rated themselves as low in strategies socio-cultural in nature. The results of this needs assessment will be used to inform implications for future practice for this midwestern school district.
Keywords: Culturally Responsive, Culturally Responsive Teaching, Self-Efficacy, Culturally Responsive Teaching Self-Efficacy